Digital Public Diplomacy Narratives: Content Analysis of Indonesian Embassy’s Engagement in the U.S. via @IndonesiainDC - Anak Agung Mia Intentilia (Politicos: Jurnal Politik Dan Pemerintahan, 2026)
This study examines digital public diplomacy narratives of Indonesian Embassy abroad through a case study of the Instagram account @IndonesiainDC, managed by the Embassy of Indonesia in Washington, D.C, the United States of America (U.S.). Using a descriptive qualitative approach with content analysis, the research analyzes posts published between 19 September 2025 and 31 December 2025, a period marked by the appointment of Ambassador Dwisuryo Indroyono Soesilo after a two?year vacancy. The study applies Cull's (2009) taxonomy of public diplomacy (listening, advocacy, cultural diplomacy, exchange diplomacy, and international broadcasting) to assess how the Embassy projects Indonesia’s identity, communicates policy priorities, and engages with foreign publics. Findings reveal that @IndonesiainDC actively employs all five functions of Cull’s taxonomy. Listening is reflected in diaspora engagement and informal community events; advocacy appears in posts promoting Indonesia’s positions on critical minerals, palm oil sustainability, and gender equality; cultural diplomacy is evident in language programs, performing arts, gastrodiplomacy, and museum collaborations; exchange diplomacy emerges through symbolic gestures such as university visits and structured initiatives like Young Southeast Asian Leaders Initiative (YSEALI) and free Bahasa Indonesia (Indonesian language) courses; and international broadcasting is demonstrated in Ambassadorial announcements, Embassy closures, and diplomatic milestones. Beyond Cull’s framework, this account also engages in hybrid practices such as webinars for Indonesian producers, knowledge diplomacy through academic collaboration, and ceremonial protocol functions, highlighting the evolving nature of digital diplomacy. This case contributes to the broader understanding of soft power and digital diplomacy in the field of International Relations, showing how Embassy adapts traditional functions to contemporary digital narratives.